Humans, machines, and double standards? The moral evaluation of the actions of autonomous vehicles, anthropomorphized autonomous vehicles, and human drivers in road-accident dilemmas - Mayer, Maike M.; Buchner, Axel; Bell, Raoul (Frontiers in Psychology, 2023)
A more critical evaluation of the actions of autonomous vehicles in comparison to those of human drivers in accident scenarios may complicate the introduction of autonomous vehicles into daily traffic. In two experiments, we tested whether the evaluation of actions in road-accident scenarios differs as a function of whether the actions were performed by human drivers or autonomous vehicles. Participants judged how morally adequate they found the actions of a non-anthropomorphized autonomous vehicle (Experiments 1 and 2), an anthropomorphized autonomous vehicle (Experiment 2), and a human driver (Experiments 1 and 2) in otherwise identical road-accident scenarios. The more lives were spared, the better the action was evaluated irrespective of the agent. However, regardless of the specific action that was chosen, the actions of the human driver were always considered more morally justifiable than the corresponding actions of the autonomous vehicle. The differences in the moral evaluations between the human driver and the autonomous vehicle was reduced, albeit not completely eliminated, when the autonomous vehicle was anthropomorphized (Experiment 2). Anthropomorphizing autonomous vehicles may thus influence the processes underlying moral judgments about the actions of autonomous vehicles such that the actions of anthropomorphized autonomous vehicles appear closer in moral justifiability to the actions of humans. The observed differences in the moral evaluation of the actions of human drivers and autonomous vehicles could cause a more critical public response to accidents involving autonomous vehicles compared to those involving human drivers which might be reduced by anthropomorphizing the autonomous vehicles.